Fungal Kinases With a Sweet Tooth: Pleiotropic Roles of Their Phosphorylated Inositol Sugar Products in the Pathogenicity of Cryptococcus neoformans Present Novel Drug Targeting Opportunities - Lev, Sophie; Li, Cecilia; Desmarini, Desmarini; Sorrell, Tania C.; Saiardi, Adolfo; Djordjevic, Julianne T. (Frontiers in Cellular and Infection Microbiology, 2019)
Invasive fungal pathogens cause more than 300 million serious human infections and 1.6 million deaths per year. A clearer understanding of the mechanisms by which these fungi cause disease is needed to identify novel targets for urgently needed therapies. Kinases are key components of the signalling and metabolic circuitry of eukaryotic cells, which include fungi, and kinase inhibition is currently being exploited for the treatment of human diseases. Inhibiting evolutionarily divergent kinases in fungal pathogens is a promising avenue for antifungal drug development. One such group of kinases is the phospholipase C1-dependent inositol polyphosphate kinases (IPKs), which act sequentially to transfer a phosphoryl group to a pre-phosphorylated inositol sugar (IP). This review focuses on the roles of fungal IPKs and their IP products in fungal pathogenicity, as determined predominantly from studies performed in the model fungal pathogen Cryptococcus neoformans, and compares them to what is known in non-pathogenic model fungi and mammalian cells to highlight potential drug targeting opportunities.